The Using Miniature Traditional Houses on Increasing Understanding of the Concept of Socio-Cultural Diversity - Rahmawati, Anisah; Tetep; Mulyana, Eldi (SAHUR Journal, 2023)
Indonesia is rich in diversity, which makes the teaching materials more numerous, causing students' understanding of the concept of socio-cultural diversity to be low. This research has the objective of examining the influence of miniature traditional houses on increasing the understanding of the concept of socio-cultural diversity among students at SMPN 5 Garut. The research method used was a quasi-experimental study with a "non-equivalent control group design", The sample was selected using the purposive sampling technique. Class VII E is the experimental class, and class VII G is the control class. Instruments are used in the form of observation, tests, and documentation. Data analysis techniques include the normality test, the homogeneity test, the gain test, and the T-test. The results of testing the hypothesis related to the effect of increasing the use of miniature traditional houses on increasing the understanding of the concept of socio-cultural diversity in students at SMPN 5 Garut are in accordance with the gain test results obtained, namely the N-Gain Score in the experimental class with this medium category indicating that there is an increase in understanding of the concept of socio-cultural diversity in the experimental class, while the N-Gain Score in the control class with this low category shows that there is no increase in students' understanding of the concept of socio-cultural diversity. This study resulted in Ho being rejected and Ha being accepted, so it can be concluded that Ho was accepted and Ha was accepted, so it can be concluded that there is an influence of miniature traditional houses in enhancing the concept of socio-cultural diversity.